Photovoltaic effect in p–SiC/p–Si heterojunction - Kozlovskyi, A.A.; Semenov, A.V.; Puzikov, V.M. (Functional Materials, 2013)
The photovoltaic effect of isotype heterojunction with hole conductivity formed films of nanocrystallinep–21R–SiC, deposited on single-crystal substrate of p–Si, has been studied (heterojunction p–SiC/p–Si). The films were prepared by direct ion deposition. The features of the current-voltage and the photovoltaic characteristics of the heterostructure p–SiC/p–Si were explained by the effect of the potential barriers, caused by band offsets in the contact region, on the migration of charge carriers through the heterojunction.